Transient current similarity based protection for wind farm transmission lines. (1st September 2018) - Jia, Ke; Li, Yanbin; Fang, Yu; Zheng, Liming; Bi, Tianshu; Yang, Qixun
Highlights: Problem of traditional line current differential relay is analyzed. A transient current similarity based protection is proposed for wind farm transmission lines. The correlation coefficient is adopted to calculate the similarity of fault transients. Field testing data is used to prove the proposed method. The novel protection offers accurate performance considering all the possible influence factors. Abstract: Large-scale wind farms are usually integrated into the transmission system. Applying traditional steady-state power-frequency based protection strategies in these transmission lines creates challenges such as: (1) the fault current of the wind farm might be dominated by non-power-frequency components caused by the activation of their own protection systems during fault ride through (FRT). The frequency of the dominant component is determined by the rotor speed at the fault inception and might vary from 0.7 to 1.3 times the power frequency. This will create errors in phasors calculated at the power-frequency. (2) The steady-state fault current angles of wind farms are fully controlled by their power converters. The variety of control actions of the different converters during FRT makes these phase angles greatly deviate from those of the synchronous generators. Protection systems that use double-ended phasors such as current differential schemes will suffer from low sensitivity or even malfunction when large-scale wind farms are integrated. Therefore, a novel full-time transient current waveform similarity based protection scheme is proposed to deal with these issues. The full-time current protection scheme uses both the power-frequency and non-power-frequency characteristics and can therefore reduce the influence of power-frequency phasor calculation errors to a minimum. The proposed method uses the transient current (within 10 ms after the fault inception) and is ignores the features of the steady-state fault current. In other words, the proposed protection is suitable for wind farms with a variety of controls. In the proposed method, the correlation coefficient index is used to calculate the similarity of the transient current signals at both ends of the line. Both experimental and field testing results show that using a common sampling frequency, the proposed protection scheme only uses current information and can correctly identify all types of external and internal line faults in a short period of time and can offer better performance for high fault resistance and noise, both for different types of wind farms. All these features and contributions make the new protection feasible for industry application.